Servant Leadership: Its Role on Organizational Citizenship Behavior through Job Satisfaction and Organizational Commitment - Sutanto, Eddy Madiono; Hoo, Vincentius Reyner Budi Saputra (Jurnal Manajemen Indonesia, 2024)
This research is based on the gaps and aims to recognize the relationship between servant leadership on organizational citizenship behavior and servant leadership on organizational citizenship behavior through job satisfaction and organizational commitment as mediation variables. There are research gaps between servant leadership and organizational citizenship behavior. The research confirms that servant leadership has no impact on organizational citizenship behavior. However, job satisfaction and organizational commitment are crucial and significant in that relationship. The research uses quantitative research with a purposive sampling technique. The population is employees in Surabaya, with 37 respondents as a sample. The data processing technique uses SmartPLS. The results indicate that servant leadership has no impact on organizational citizenship behavior. In addition, when mediated by job satisfaction and organizational commitment, servant leadership significantly impacts organizational citizenship behavior. Servant leadership itself has no significant impact on organizational citizenship behavior. However, the existence of other beneficial variables is necessary. Further research needs to get consistent results.